Light exposure of roots in aeroponics enhances the accumulation of phytochemicals in aboveground parts of the medicinal plants Artemisia annua and Hypericum perforatum - Paponov, Martina; Ziegler, Jörg; Paponov, Ivan A. (Frontiers in Plant Science, 2023)
Light acts as a trigger to enhance the accumulation of secondary compounds in the aboveground part of plants; however, whether a similar triggering effect occurs in roots is unclear. Using an aeroponic setup, we investigated the effect of long-term exposure of roots to LED lighting of different wavelengths on the growth and phytochemical composition of two high-value medicinal plants, Artemisia annua and Hypericum perforatum. In A. annua, root exposure to white, blue, and red light enhanced the accumulation of artemisinin in the shoots by 2.3-, 2.5-, and 1.9-fold, respectively. In H. perforatum, root exposure to white, blue, red, and green light enhanced the accumulation of coumaroylquinic acid in leaves by 89, 65, 84, and 74%, respectively. Root lighting also increased flavonol concentrations. In contrast to its effects in the shoots, root illumination did not change phytochemical composition in the roots or root exudates. Thus, root illumination induces a systemic response, resulting in modulation of the phytochemical composition in distal tissues remote from the light exposure site.